PENGARUH PEMBIAYAAN FINTECH SYARIAH TERHADAP MODAL KERJA, OMZET PENJUALAN, DAN LABA BERSIH UKM (STUDI PADA ALAMI SHARIA) - Nauvalsev Abdul Purba; Anna Sardiana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2021)
The presence of a number of fintech companies contributes to the development of Small and Medium Enterprises (UKM) in meeting their business capital needs. This answered an opinion which stated that SMEs have problems in accessing finance, one of which is the lack of access to formal sources of funds, either due to the absence of banks in remote areas or the unavailability of adequate information. There is so much potential for Islamic fintech financing that it deserves attention, but to this day there are still few scientific papers published to see whether Islamic fintech has a role in developing the financial performance of SMEs. Data analysis techniques and hypothesis testing in this study used the SmartPLS program. There is sufficient evidence that financing measures can improve the financial performance of SMEs in terms of working capital performance and sales turnover, while for net income it takes time to see the positive trend of PT Alami Fintek Sharia financing.